Effectiveness of international virtual training on biorisk management in the context of COVID-19 - Qasmi, Shamsul Arfin; Standley, Claire; Mohsin, Saima; Sarwar, Samreen; Malik, Laila; Aziz, Fatima (Frontiers in Public Health, 2022)
Objective: To increase the basic knowledge and standards of Biosafety and Biosecurity practices, risk assessment and control measures during covid-19 with the help of virtual training. Introduction: A highly interactive virtual training workshop on effectiveness of Bio-Risk Management (BRM) during COVID-19 was conducted through active learning strategies that connect speakers with participants by developing poll questions, pre and post-assessment and feedbacks regarding Speaker’s knowledge and presentation skills. The training covered a broad range of biosafety, biosecurity, and risk assessment from national to international guidelines in this regard. Methods: There were 52 Participants from different institutes across Pakistan and from abroad as well. The participants were selected through proper channels at national level. The pre & post assessment test was conducted at the beginning and the end of overall series comprised on similar MCQs which were provided to every participant to ascertain the impact of awareness. Also, the participants were asked to submit their feedbacks regarding Speakers overall presentation and their rating measured on five-point Likert scale (1-Poor, 2-Fair, 3-Good, 4-Very Good & 5-Excellent). The reliability of the Likert scale was estimated using Cronbach’s alpha. Overall training evaluated by using Microsoft Excel & IBM-SPSS version 23. Results: The pre- and post-assessment at the beginning and end of the webinar of each participant were compared the impact of training on awareness, analysis of these results were obtained through a paired t-test yielded a highly significant P value of 0.000 where the Level of significance determined by using 95% confidence interval. The obtained Cronbach’s alpha score of > 0.80, indicating the high reliability of the generated feedback evaluation. Conclusion: This International Virtual Training (IVT) on biosafety and biosecurity in context of the ongoing COVID-19 pandemic has proved beneficial for laboratories professionals exposed to potentially infectious material by increasing level of awareness.